2006
DOI: 10.1143/jjap.45.l422
|View full text |Cite
|
Sign up to set email alerts
|

Intense Terahertz Pulses from Large-Aperture Antenna with Interdigitated Electrodes

Abstract: We fabricated a large-aperture photoconductive terahertz (THz) emitter array on a semi-insulating GaAs substrate. The device was composed of seven 1 cm2 photoconductive antenna units having microstructured interdigitated electrodes with 10 µm lines and spaces. By illuminating it with amplified femtosecond optical pulses, a large THz field comparable to that obtained from conventional large-aperture photoconductive antennas was obtained at a bias voltage as low as 30 V. The coherent superposition of the output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…By inverting the bias voltage applied to the central unit, coherent synthesis of output from the seven units leads to annular profiles and smaller spot sizes of the focused THz field. Putting the present results together with the previous observation on time-domain coherent superposition [1], it is shown that spatio-temporal coherent systhesis can be performed using THz emitter arrays.…”
supporting
confidence: 76%
“…By inverting the bias voltage applied to the central unit, coherent synthesis of output from the seven units leads to annular profiles and smaller spot sizes of the focused THz field. Putting the present results together with the previous observation on time-domain coherent superposition [1], it is shown that spatio-temporal coherent systhesis can be performed using THz emitter arrays.…”
supporting
confidence: 76%
“…In recent years, improvement in the various fields of THz research has been achieved with the development of an advanced laser source with femtosecond ( fs ) pulses123. The observation of THz waves between the microwave and infrared regions has motivated further expansion in research directions not previously considered, such as carrier dynamics with ~ ps lifetimes and applications in biomedical research using extremely low energy (~ meV).…”
mentioning
confidence: 99%
“…This is similar to the behavior of large aperture emitters [32]. In another experiment, seven emitters of 1 cm 2 area have been combined to an array of large enough area to reduce the saturation effects by expanding the NIR beam [119]. However, only 1 kV/cm output fields could be achieved, possibly because of difficulties to focus the THz beam tightly.…”
Section: Operation Of Scalable Microstructured Emitters With Amplifiementioning
confidence: 54%